Analisis Statistik Untuk Mendapatkan Waktu Optimal Dari Losstime Dalam Memenuhi Produksi Penambangan Batubara Di Area Pit Timur PT. Artamulia Tatapratama - Rukia Pinda Sari; Murad Murad; Adree Octova (Departemen Teknik Pertambangan FT UNP, 2018)
Based on data of coal production at PT. Artamulia Tatapratama (ATP) from January to May 2017. The coal production target was not reached in February-May 2017, while coal production in January 2017 was achieved. This is caused by several constraints in coal production activities, because of these constraints cause effective working hours at PT. ATP is reduced. From this problem, it is necessary to analyze the optimal time from losstime to reach the established coal production plan. To get the optimal time in achieving the production plan is done by multiple linear regression analysis, the results obtained from this analysis is the maximum limit of the time losstime, and to determine the optimal time of losstime is using simulation of linear equation regression. The optimal timing of the digging equipment in achieving the daily production of coal based on the results of the simulation of statistical analysis when idle time of 3 units of unloading equipment operates for 7.67 hours, the delay time allowed from the equipment is 12.99 hours, while if the delay time is 14.78 hours, the idle time allowed only 6.03. After knowing the problem causing decrease of working time of digging and unloading equipment (losstime), it is necessary to improve corrective action to be applied in the field.Keywords: Production, Losstime, Statistical Analysis, Optimal Time, Coal Mining